2021
DOI: 10.1111/pde.14782
|View full text |Cite
|
Sign up to set email alerts
|

Virtual group visits to reduce psychosocial distress and racial disparities in pediatric vitiligo and alopecia areata patients

Abstract: We examined the potential for virtual, pediatric group visits to reduce racial disparities in psychosocial isolation and access to care among children of color with pediatric vitiligo and alopecia areata as well as their caregivers. We have conducted 10 visits with 30 pediatric skin of color patients between 5 and 16 years old: 18 patients with alopecia areata, 12 with vitiligo, 59% female, 64% Black, and 23% Latinx, and 33 parents. After the visits, children and parents felt they had more people they knew and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Prior to the group visit, 90% of children and 85% of parents stated they knew few others with vitiligo. A post-session survey revealed the majority of patients and their parents found the visits helpful and would attend another group visit [41]. More research is needed to investigate these and other interventions in children with vitiligo and other dermatologic conditions.…”
Section: Dermatology Online Journal || Reviewmentioning
confidence: 99%
“…Prior to the group visit, 90% of children and 85% of parents stated they knew few others with vitiligo. A post-session survey revealed the majority of patients and their parents found the visits helpful and would attend another group visit [41]. More research is needed to investigate these and other interventions in children with vitiligo and other dermatologic conditions.…”
Section: Dermatology Online Journal || Reviewmentioning
confidence: 99%
“…2 Few studies have explored the role of this care model in patients with alopecia. 3,4 The aim of our study is to summarize patient satisfaction with a multidisciplinary SMA for patients with alopecia areata (AA) and frontal fibrosing alopecia (FFA).…”
mentioning
confidence: 99%
“…Khosla and colleagues found that virtual group support visits may reduce psychosocial isolation and improve access to care for children with vitiligo (as well as their parents), particularly among those from non-White racial backgrounds. 2 Moreover, a 1993-2010 National Ambulatory Medical Care Survey study revealed that African American and Hispanic patients were less likely to have a procedure performed for dyschromia (N=24.7M, P<0.01), presumably owed to potential adverse effects in darkerskinned populations, yet more favorable combination regimens also remain underutilized in these groups. 3 Kang et al additionally highlight that more than a quarter of these patients rely on Medicare (9%) or self-pay (17%), which may alone pose significant barriers to cosmetic dyschromia treatment.…”
mentioning
confidence: 99%